Chasing ghosts: the phylogeny of Amaurobioidinae ghost spiders (Araneae, Anyphaenidae) - Labarque, Facundo Martín (2015)
The family Anyphaenidae, also known as ghost spiders, includes a diverse array of nocturnal cursorial spiders that actively hunt on vegetation. The family is mostly distributed in the Americas and has been traditionally divided into three subfamilies. The mostly tropical and North American Anyphaeninae and the Amaurobioidinae, primarily distributed in southern South America, hold the bulk of the diversity, while the Malenellininae includes a single Chilean species. Here, we use a combined morphological and molecular approach to infer the relationships of the subfamily Amaurobioidinae and examine the delimitation of contentious genera. The morphological characters include both genitalic and somatic morphology, whereas molecular data include four markers, two mitochondrial (COI, 16S) and two nuclear (28S, H3). All our analyses agree on the monophyly of Amaurobioidinae, Amaurobioidini, Gayennini, the genera Negayan, Amaurobioides, Josa, Araiya, Arachosia and Monapia, as well as the paraphyly of Anyphaeninae. The total evidence analysis supports the novel placement of Josa as the sister group of both tribes Amaurobioidini and Gayennini, most of the previously known intergeneric relationships within Gayennini, and a clade of Amaurobioidini with a projecting ocular area, including Aysenoides, Axyracrus, Amaurobioides and Aysenia. The sequence data solve the puzzling placement of Philisca puconensis, here transferred to Tomopisthes, and Tasata chiloensis, transferred to Oxysoma. The advantages of the total evidence phylogenetic approach and the evolution of the male copulatory organ are discussed.